Nature as “grundnorm” of global constitutionalism: contributions from the global south/ La naturaleza como grundnorm del constitucionalismo global: contribuciones desde el sur global - Carducci, Michele; Patricia Castillo Amaya, Lidia (Revista Brasileira de Direito, 2016)
Abstract: Unrelenting consumption and excessive exploitation of natural resources and their interconnection with the intensification of global inequalities seem to be leading contemporary civilization to an imminent collapse.  How does constitutionalism address these ecology related issues? The purpose of this paper is two-fold: Firstly, it aims at uncovering the semantics of  “constitution and nature” within constitutional law. The authors argue that mainstream dialogue-based approach (trans-national judicial dialogue) to global constitutionalism is actually based on a eurocentric and anthropocentric logos that excludes nature and reduces her to a simple object. Secondly, it discusses two original alternative proposals emerged  from the global South: the constitutionalism for biodiversity of the Andean Latin American countries and the African Union's project to establish an International Constitutional Court. While the Andean constitutions prioritize the discussion on the “ecological deficit” and place nature as their “Grundnorm”, the African proposal suggests the creation of a universal judicial mechanism for the protection of the “right to democracy”. Given the centrality of nature within the innovative Andean constitutional design and the universalistic potential of democratic forms of public deliberation, these two propositions advance a novel approach to constitutionalism with a truly global scope, capable of both facing up impending ecological threats as well as pursuing dignity, justice and equality at global level.Keywords: Judicial Dialogue, Global Constitutionalism, Rights of Nature, Right to Democracy.  Resumen: El incesante consumo y la explotación excesiva de los recursos naturales y su interconexión con la intensificación de la desigualdades a nivel mundial parecen estar llevando a nuestra civilización contemporánea hacia su colopaso inminente. Cómo enfrenta el constitucionalismo actual estos problemas ecológicos? Este trabajo tiene una doble finalidad. Primero, pretende descubrir cuáles semtánicas de “constitución y naturaleza” se encuentran en el derecho constitucional actual. Los autores argumentan que la visión dominante del constitutionalismo global, en su perspectiva dialógica (diálogo transnacional entre Cortes), está basada en un logos eurocéntrico y antropocéntrico que excluye a la naturaleza y la convierte en un simple objeto. Segundo, busca discutir dos originales propuestas alternativas surgidas en el Sur global: por un lado, del constitucionalismo de la biodiversidad de los países andinos latinoamericanos, y  por otro, la propuesta de la Uníón Africana de crear de una Corte Constitutional Internacional. Mientras que las constituciones andinas priorizan la discusión sobre del “déficit ecológico” y colocan a la naturaleza como su “Grundnorm”, la propuesta africana considera la creación de un mecanismo judicial universal de protección del “derecho a la democracia”. Dada la centralidad que el innovador diseño constitucional andino da a la naturaleza y el potencial universalista de las formas democráticas de deliberación pública, estas propuestas promueven una  nueva perspectiva para el constitucionalismo con alcance realmente globa y capaz de enfrentar las amenzas ecológicas inminentes, así como perseguir la dignidad, la justicia y la igualdad a nivel global.  Palabras Llave: constitucionalismo global, diálogo Judicial, derechos de la naturaleza, derecho a la democracia.